Pursuing a target with one's eyes helps judge its velocity. (December 2022) - de la Malla, Cristina; Smeets, Jeroen B. J.; Brenner, Eli
When intercepting moving targets, people perform slightly better if they follow their natural tendency to pursue the target with their eyes. Is this because the velocity is judged more precisely when pursuing the target? To find out, we compared how well people could determine which of two sequentially presented moving bars was moving faster. There was always also a static bar on the screen. People judged the moving bar's velocity about 10% more precisely when pursuing it than when fixating the static bar.